2013
DOI: 10.1103/physrevb.87.035131
|View full text |Cite
|
Sign up to set email alerts
|

Field effect on surface states in a doped Mott-insulator thin film

Abstract: Surface effects of a doped thin film made of a strongly correlated material are investigated both in the absence and presence of a perpendicular electric field. We use an inhomogeneous Gutzwiller approximation for a single band Hubbard model in order to describe correlation effects. For low doping, the bulk value of the quasiparticle weight is recovered exponentially deep into the slab, but with increasing doping, additional Friedel oscillations appear near the surface. We show that the inverse correlation len… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…For larger fields the discrepancy between the DMFT and ILA is significant in a narrower region close to the surface. The main reason for this is the existence of highly-doped regions (close to the surfaces) in which the correlation length is smaller, 22 which limits the discrepancy between the two approaches to only the surface layer. We expect that the discrepancy between the DMFT and ILA will be larger whenever the correlation length is larger, in particular at very low temperatures and when the first order nature of the transition is weaker.…”
Section: A Coexistencementioning
confidence: 99%
See 1 more Smart Citation
“…For larger fields the discrepancy between the DMFT and ILA is significant in a narrower region close to the surface. The main reason for this is the existence of highly-doped regions (close to the surfaces) in which the correlation length is smaller, 22 which limits the discrepancy between the two approaches to only the surface layer. We expect that the discrepancy between the DMFT and ILA will be larger whenever the correlation length is larger, in particular at very low temperatures and when the first order nature of the transition is weaker.…”
Section: A Coexistencementioning
confidence: 99%
“…The Gutzwiller approximation [14][15][16] and slave boson techniques 17,18 have been used to treat the low-energy physics of bulk materials and -more recently -thin films [19][20][21][22][23][24] in the presence of an electric field. 21,22 The slave boson approach has been extended to allow access to higher-energy excitations 25 , while the Gutzwiller approximation only provides insight into the metallic state. Other notable approaches include the density renormalization group (DMRG), which works best for one-dimensional systems.…”
Section: Introductionmentioning
confidence: 99%
“…. This means that small changes to the carrier density (CD) can modify the electronic ground state and properties considerably 18,24,25 . Thus, accurate measurements of CD as a function of intrinsic changes or external stimuli can help to understand these systems, as exemplified in other correlated electron systems, such as cuprates 26 , heavy fermions 27 interface of LAO/STO 28,29 .…”
Section: -23mentioning
confidence: 99%
“…It is accepted that even if the transition is not purely electronic, Mott-Hubbard electron-electron correlations play an important role in the evolution of the phase transition and properties of the insulating state in VO 2 21 22 23 . This means that small changes to the carrier density (CD) can modify the electronic ground state and properties considerably 18 24 25 . Thus, accurate measurements of CD as a function of intrinsic changes or external stimuli can help to understand these systems, as exemplified in other correlated electron systems, such as cuprates 26 , heavy fermions 27 and interface of LAO/STO 28 29 .…”
mentioning
confidence: 99%
“…It was shown that the perturbation induced by the surface propagates exponentially deep inside the bulk material with a well-defined length scale which is a function only of bulk properties and not of the strength of the perturbation [4]. Moreover, the effect of the charge transfer from less correlated to more correlated regions has been studied for both single-band and two-band Hubbard models, and it was shown to be more pronounced when an external electric field is applied [5][6][7].…”
Section: Introductionmentioning
confidence: 99%